Identifikasi Senyawa Metabolit Sekunder dan Analisis Total Fenolik Ekstrak Metanol Daun Sacha Inchi (Plukenetia volubilis linneo) yang Tumbuh di Gorontalo - Nur Riska Apriana; Nurhayati Bialangi; La Alio; Yuzda K Salimi; La Ode Aman; Ahmad Kadir Kilo (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Sacha inchi (Plukenetia volubilis Linneo) is a plant from the Euphorbiaceae family known for its green star-shaped fruit and brown seeds. This plant has high nutritional value and significant antioxidant activity (Nuha and Sriwidodo 2022). This study aims to identify secondary metabolite compounds and determine the total phenolic content of the methanol extract of Plukenetia volubilis Linneo leaves. The samples were extracted using the maceration method, then phytochemical tests and total phenolic content analysis were carried out using the Folin-Ciocalteu method (Sari et al. 2021). The results of the phytochemical test showed that the methanol extract of sacha inchi leaves contained secondary metabolite compounds such as alkaloids, flavonoids, saponins, and tannins. The total phenolic content obtained from the extract was 19.94%, which indicates the potential for high antioxidant activity. The results of this study indicate that sacha inchi leaves have the potential to be developed as a source of natural bioactive compounds that are beneficial to health.